Penggunaan Metode Akustik Untuk Menduga Stok Sumberdaya Ikan Pelagis Di Perairan Bengkalis Kabupaten Bengkalis Provinsi Riau - Arthur Brown; Pareng Rengi; Bustari Bustari (Berkala Perikanan Terubuk, 2015)
Fish stock estimates based on hydroacoustic study in two consecutive years in the studied area, especially in the waters northeast of the island Bengkalis with total area 4.975 km2,  number of stocks in 2012 as much as 9.378 tons of fish a density of 0,44 tonnes / km2 and in 2013 obtained value of the stock of 8.847 tonnes of fish densities of 0,43 tonnes / km2.  The spread horizontally density of pelagic fish in the eastern part of Bengkalis Island tends to decrease as the depth of the density;  conditions at depth 5-15 meters was the highest density layer with a difference of 16.33 individuals / m3.  The density of fish on the evening ranged along 2012 from 0.71 to 15.34 fish / m3, while during the day from 0.78 to 31.67 fish / m3. In 2013 the level of the fish tan evenings from 0.59 to 14.87 m3, daytime 0,67-28,68m3.  With the size of the stock in the period 2012 to 2013 were above 8847 tons per year with an estimated utilization rate has reached 90%. Strenght target value (TS) are considered as small pelagic fish was from 43.94 to 58.66 dB in the surface layer.  Base on the  business aspects of fishing which was  represented by talang gillnet  obtain  results of the analysis are Benefit Cost Ratio (BCR) 1.2; Financial Rate of Return (FRR) 16%; Payback Period of Capital (PPC) or a 6.3-year despite venture capital can be returned but relatively long repayment period and it indicates that the catches were declining.